Autobiographical memory and dissociation in borderline personality disorder. - Jones, B; Heard, H; Startup, M; Swales, M; Williams, J; Jones, R (1999)
BACKGROUND: This study investigated whether individuals with borderline personality disorder (BPD) tend to be overgeneral in their autobiographical recall and whether the extent of their overgeneral recall covaries with their susceptibilities to dissociative experiences, as expected on theoretical grounds. METHODS: Twenty-three patients with BPD and 23 matched controls completed the Autobiographical Memory Test (AMT) and self-report measures of depression, anxiety, trait anger and dissociative experiences. RESULTS: Participants with BPD scored significantly higher than the control group on the measures of depression, anxiety, trait anger, and dissociative experiences and also retrieved significantly more general memories on the AMT. The number of general memories retrieved by the BPD group correlated significantly with their dissociation scores but not with their scores on mood measures. CONCLUSIONS: Patients with BPD have difficulties in recalling specific autobiographical memories. These difficulties are related to their tendency to dissociate and may help them to avoid episodic information that would evoke acutely negative affect.